Percepções de profissionais da estratégia saúde da família sobre atenção à saúde bucal da gestante - Henrique, Fabiana Silva (2014)
This study has investigated the perceptions of physicians, nurses and dentists from the Family Health Strategy – FHS, on attention to the oral health of pregnant women, using a qualitative approach. Data collection was performed at Basic Health Units of Regional III, in the city of Fortaleza, in the period September-November 2013, by using semi-structured interviews, which were taped, transcribed and then analyzed through thematic analysis of Minayo. The content and meaning of the statements were grouped into thematic groups and then considering the similarities and differences, were organized into three categories: The way of working of the FHS team for the oral health of pregnant women; Perceptions of FHS professionals about oral health during pregnancy and the structure and organization of services. The results showed the need for joint work of professionals in activities to promote oral health of pregnant women, having been stressed the importance of performing dental treatment during pregnancy, considering that oral health of pregnant women can affect their overall health and of your baby. While some doctors and nurses FHS perform oral hygiene instructions and either refer the pregnant women to dental services, others simply adopt this approach considering any oral complaints or problems. Pregnant women’s self-care in relation to oral health was deemed deficient by professionals and should be reinforced during the consultations and collective activities. Myths still persist among pregnant women who understand that they cannot undergo dental treatment and that pregnancy causes oral problems. The great demand, lack of supplies and equipment damaged were constantly difficulties for beginning, follow-up and completion of the treatments and educational activities. We conclude that the FHS presents the conditions for integrated oral health of pregnant women because the presence of a multidisciplinary team and the great possibility of interaction between the dentist and the professionals who perform prenatal. However, there is need to organize demand and invest in ongoing professional training, physical structure, equipment and inputs of units.